Being a teacher in public schools in Honduras. A biographical-narrative study (Práxis Educativa, 2025)
In this article, seven teachers describe the meanings of their work as teachers in public schools in the Honduran educational system. The paper presents qualitative research carried out using the biographical-narrative method. The instruments used to collect information were semi-structured interviews and life stories. The results show that the teaching vocation arises from the desire to contribute to the country's development. On the other hand, the teachers explain the difficulties faced while carrying out the educational practice to the lack of governmental support, which deteriorates the teaching system. In addition, it becomes necessary a constant preparation to provide higher-quality education. The discussion agrees with other international studies and concludes that the State must commit itself by providing tangible support to promote teacher training based on social justice.Keywords: Teachers. Education. Honduras. Social justice. Narratives. Teaching practice.